Oversight Hearing on the Reauthorization of the Higher Education Act in Burlington, VT. Hearing before the Subcommittee on Postsecondary Education of the Committee on Education and Labor. House of Representatives, Ninety-Ninth Congress, Second Session (Burlington, Vermont) - Congress of the U.S., Washington, DC. House Committee on Education and Labor; Congress of the U.S., Washington, DC. House Committee on Education and Labor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Hearings on reauthorization of the Higher Education Act that were held in Burlington, Vermont, in 1986 are presented. Included is Vermont's unified position concerning the relative merits of House and Senate versions of the Higher Education Act. In Vermont, a special committee composed of representatives from all sectors of higher education monitored the Reauthorization Act. It is noted that there has been greater reliance on loan programs and that the value of Pell grants has dropped by 26% in the last 5 years, because of the effects of the constant dollar. Attention is directed to the consequences of the Gramm-Rudman-Hollings act and current budget proposals. It is argued that the Reagan Administration's student aid proposals would eliminate or reduce awards for over 3 million students, whose only alternative source of assistance would be loans carrying a significantly higher burden of debt. Loan availability would be drastically curtailed, however, if the proposed Guaranteed Student Loan changes cause lenders to pull out and collapse the program. Twelve categorical support programs would be eliminated by recisions in the current fiscal year (FY) 1986 budget, and no funds would be requested for them in FY 1987. Suggestions are offered concerning eligibility for Pell grants and program administration. (SW)
Availability: Superintendent of Documents, Congressional Sales Office, U.S. Government Printing Office, Washington, DC 20402.
ERIC Note: Serial No. 99-112.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Budgets; College Students; Credit (Finance); Debt (Financial); Educational Finance; Eligibility; Federal Aid; Federal Legislation; Financial Aid Applicants; Financial Policy; Government School Relationship; Hearings; Higher Education; Policy Formation; Public Policy; Student Financial Aid; Student Loan Programs; Higher Education Act 1965; Congress 99th -- Pell Grant Program -- Reagan Administration -- Vermont; Legal/Legislative/Regulatory Materials